1980
DOI: 10.1016/0160-7995(80)90030-1
|View full text |Cite
|
Sign up to set email alerts
|

Interrelation between health and population: Observations derived from field experiences

Abstract: Ahtract-This paper presents information and concepts concerning the health of populations in less developed countries as background for discussions of more focused and detailed papers on these and related subjects.It begins with a review of health status and trends in developing countries since 1950. followed by a section identifying the major health problems and their causes.The third part includes analyses of associations between health resources. water and sanitation facilities. food availability. and econo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…But in 1970-1975 the most important indicator was percentage of the adult popUlation literate, which explained 78% of the variation by itself. In addition, the model showed that sanitation variables began to appear as significant correlates of life expectancy in the later period, playing a larger role than income per capita (31).…”
Section: Changes In Determinants Over Timementioning
confidence: 98%
“…But in 1970-1975 the most important indicator was percentage of the adult popUlation literate, which explained 78% of the variation by itself. In addition, the model showed that sanitation variables began to appear as significant correlates of life expectancy in the later period, playing a larger role than income per capita (31).…”
Section: Changes In Determinants Over Timementioning
confidence: 98%
“…Such a decision requires determination of the costs and health effects of other health programs in West Java. In an earlier study of Javanese health programs, costs and effectiveness of health interventions were calculated (Grosse 1980;Grosse, DeVries and Tilden, 1981). A rough comparison between the vitamin A programs and the interventions examined in the other study (medical care reorganization, nutritional supplements, immunization and sanitation) indicated that the vitamin A programs have the potential to reduce child mortality at very much lower cost.…”
Section: Discussionmentioning
confidence: 99%
“…It is assumed that under conditions of famine people will first decrease their activities to try to balance intake and expenditure of energy, so that their health will not be seriously A further deterioration of the food supply, however, will rapidly increase mortality (see Table 1). On account of experiences in other countries (Grosse 1980;Stock 1985; Walsh and Warren 1980), it is assumed that an improvement of medical services will only afFect infant mortality. Migration constitutes an important drain on the population, especially for ages 16-40.…”
Section: The Modelmentioning
confidence: 99%